Предмет: Алгебра,
автор: aszx
y=3*x^2-8*x-2 y=x^2-4
y=2*x^2-6*x-1 y=x^2-2*x
Ответы
Автор ответа:
0
y=3*x^2-8*x-2 D=b^2-4ac=8^2-4*3*(-2)=88 x1=(8-корень из 88)2*3=(8-корень из 88)6 х2=(8+корень из 88)2*3=(8+корень из 88)6 y=x^2-4 D=-4*a*c=-4*1*(-4)= 16 x1=-42=-2 x2=42=2 y=2*x^2-6*x-1 D=36-4*2*(-1)=44 x1=(6-корень из 44)2*2=(6-корень из 44)4 x2=(6+корень из 44)2*2=(6+корень из 44)4 y=x^2-2*x D=4-4*1*0=4 x1= (2-2)2*1= 0 x2=(2+2)2*1=2
Похожие вопросы
Предмет: Русский язык,
автор: sasha99924
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: senkagg
Предмет: Химия,
автор: lena197612